2021
DOI: 10.3390/polym13142349
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Anilinium Ion on the Selective Polymerization of Anilinium 2-Acrylamide-2-methyl-1-propanesulfonate

Abstract: The development of anilinium 2-acrylamide-2-methyl-1-propanesulfonate (Ani-AMPS) monomer, confirmed by 1H NMR, 13C NMR, and FTIR, is systematically studied. Ani-AMPS contains two polymerizable functional groups, so it was submitted to selective polymerization either by free-radical or oxidative polymerization. Therefore, poly(anilinium 2-acrylamide-2-methyl-1-propanesulfonic) [Poly(Ani-AMPS)] and polyaniline doped with 2-acrylamide-2-methyl-1-propanesulfonic acid [PAni-AMPS] can be obtained. First, the acrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 78 publications
(113 reference statements)
2
7
0
Order By: Relevance
“…Another signal corresponding to the methylene groups is at 1.4 ppm (H 6 , 6H). The pattern, position, and integration of signals are consistent with research previously reported by our group [ 37 ], except for the integration of protons corresponding to aromatic anilinium due to differences in synthesis methodology. In the previous work, the polymerization proceeded directly from a bifunctional monomer, including anilinium ions, while in the present research, the doping was performed post-polymerization.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Another signal corresponding to the methylene groups is at 1.4 ppm (H 6 , 6H). The pattern, position, and integration of signals are consistent with research previously reported by our group [ 37 ], except for the integration of protons corresponding to aromatic anilinium due to differences in synthesis methodology. In the previous work, the polymerization proceeded directly from a bifunctional monomer, including anilinium ions, while in the present research, the doping was performed post-polymerization.…”
Section: Resultssupporting
confidence: 91%
“…Figure 5 shows the UV–Vis spectra of macro-RAFT in aqueous solution and in solid-state. In Figure 5 a, displaying the results in aqueous solution, three absorption bands are observed at 250 nm, 284 nm, and 312 nm, corresponding to the n-π* transition of N + quaternized nitrogen, the π-π* transition of anilinium ring [ 37 ], and the π-π* of C=S of CTA [ 46 ]. On the other hand, the spectrum in the solid-state has a broadband absorption between 230 and 800 nm, with a maximum at 301 nm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations